Prehistoric Predators - Black, Riley; Csotonyi, Julius, 1973- (Kennebunkport, Maine : Applesauce Press, 2015)
Provides information on prehistoric carnivores, including some lesser known ones such as the Dimetrodon Limbatus, Kryptops Palaios, and Quetzalcoatlus Northropi.
Includes index.
new kids book 2023 spring.
Ages: 8 and up.
Keywords: Predatory animals, Fossil -- Juvenile literature; Dinosaurs -- Juvenile literature; Animals, Fossil -- Juvenile literature